Analyzing Students’ Critical Thinking Pattern in Writing Argumentative Paragraph Based on Stephen Toulmin Theory - Ika Sastrawati; Uyunnasirah Hambali; Andi Bulkis Maghfirah Mannong; Haslinda Haslinda (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This study aims to examine students' critical thinking patterns in writing argumentative paragraphs using the argumentative patterns developed by Stephen Toulmin. This study used qualitative approach. To collect the data, the instrument used was students’ writing on the Academic Writing class. Hence, the third semester students were involved as the participants. Then, the collected data were analyzed focusing on the Stephen Toulmin Theory which divides the argument into six stages; claim, ground, warrant, backing, qualifier, and rebuttal. The result of this study revealed that by focusing on Stephen Toulmin's argumentative theory, students could hone their ability to think critically. This is because the elements on Stephen Toulmin’s theory were proved to strengthen students’ writing.